2014
DOI: 10.1101/gad.248492.114
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a Fanconi anemia-associated nuclease homolog bound to 5′ flap DNA: basis of interstrand cross-link repair by FAN1

Abstract: Fanconi anemia (FA) is an autosomal recessive genetic disorder caused by defects in any of 15 FA genes responsible for processing DNA interstrand cross-links (ICLs). The ultimate outcome of the FA pathway is resolution of crosslinks, which requires structure-selective nucleases. FA-associated nuclease 1 (FAN1) is believed to be recruited to lesions by a monoubiquitinated FANCI-FANCD2 (ID) complex and participates in ICL repair. Here, we determined the crystal structure of Pseudomonas aeruginosa FAN1 (PaFAN1) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 59 publications
(107 reference statements)
1
32
0
Order By: Relevance
“…Recent crystallographic data revealed that the SAP domain interacts extensively with the DNA (Gwon et al 2014;Wang et al 2014;Zhang and Walter 2014), suggesting that direct DNA binding to the ICL might be responsible for the recruitment of FAN1 to sites of DNA damage. To investigate the contribution of the UBZ and the SAP domains to the localization of FAN1 at ICLs, we studied the recruitment of human GFP-tagged FAN1 (GFP-hFAN1) to psoralen-induced ICLs in U2OS cells ( Fig.…”
Section: Fan1 Is Required For Resistance To Dna Icl-inducing Agents Imentioning
confidence: 99%
“…Recent crystallographic data revealed that the SAP domain interacts extensively with the DNA (Gwon et al 2014;Wang et al 2014;Zhang and Walter 2014), suggesting that direct DNA binding to the ICL might be responsible for the recruitment of FAN1 to sites of DNA damage. To investigate the contribution of the UBZ and the SAP domains to the localization of FAN1 at ICLs, we studied the recruitment of human GFP-tagged FAN1 (GFP-hFAN1) to psoralen-induced ICLs in U2OS cells ( Fig.…”
Section: Fan1 Is Required For Resistance To Dna Icl-inducing Agents Imentioning
confidence: 99%
“…1A) with T4 polynucleotide kinase (New England Biolabs) and [␥- 32 P]ATP and annealing with oligonucleotide III as described above. The 3Ј-labeled cross-linked substrates (Figs.…”
Section: Methodsmentioning
confidence: 99%
“…However, a number of studies suggested that the cross-link repair function of FAN1 is not within the FA pathway as: (i) homologs of FAN1 have been found in bacteria, archaea, and unicellular eukaryotes which lack FA proteins (19,(21)(22)(23), (ii) mutations in FAN1 do not cause FA, but instead a kidney disorder called karyomegalic interstitial nephritis (KIN) (24), (iii) N-terminal UBZ domain is dispensable for ICL repair, but is required for genomic maintenance, suggesting that the interaction of FAN1 with ID serves a function outside of ICL repair (25)(26)(27). Nevertheless, the sensitivity of FAN1-deficient cells to ICL-forming agents implicates FAN1 in ICL resolution independently of the FA pathway.…”
Section: Dna Synthesis (Tls) and The Second Strand Is Repaired By Hommentioning
confidence: 99%
“…FAN1 incises substrates 2-5 nucleotides into the duplex from the ss/ds junction of DNA with a 5' flap or a nick, followed by 5' to 3' exonucleolytic cleavage of the duplex even in presence of an ICL (17)(18)(19)(20)23,(32)(33)(34).…”
Section: Dna Synthesis (Tls) and The Second Strand Is Repaired By Hommentioning
confidence: 99%
See 1 more Smart Citation